Growth and infectious exposure during infancy and the risk of rheumatoid factor in adult life. Issue 3 (3rd August 2005) - Edwards, C J; Goswami, R; Goswami, P; Syddall, H; Dennison, E M; Arden, N K; Cooper, C
Abstract : Background: The contribution of the environment to rheumatoid arthritis (RA) remains uncertain. Intrauterine and early postnatal life may be important. Rheumatoid factor (RF) found in around 10% of the normal population confers a risk of developing RA and may be present years before onset of clinical disease. The immune pathology leading to RA and RF may have similar genetic and environmental influences. Objective: To measure RF in people for whom data on birth weight, infant growth, and markers of infectious exposure during infancy and childhood, had been previously recorded. Methods: 675 men and 668 women aged 59–67 years, born and still resident in Hertfordshire, UK, were studied. RF was measured with an ELISA. Associations between presence of RF, early growth, and markers of hygiene in infancy, were investigated. Results: RF was detected in 112/675 (16.6%) men and 79/668 (11.8%) women. No significant relationships existed between early growth and presence of RF in men or women. Among women, sharing a bedroom during childhood was associated with a lower risk of RF positivity (OR = 0.48, 95% CI 0.30 to 0.78, p = 0.003). Conclusions: A developing immune system exposed to increased infectious exposure is less likely to produce RF in adult life; this may reduce the pathological process which leads to RA.